Analysis of the Potential and Utilization Rate of Longtail Tuna (Thunnus tonggol) Landed at the Bungus Ocean Fishing Port (PPS), Padang City, West Sumatra Province - Brown, Arthur; Yani, Alit Hindri; Putri, Yolanda Aidina (Jurnal Perikanan dan Kelautan, 2024)
Fish resources have limits; therefore, it is necessary to carry out appropriate management so that resource utilization is sufficient for a long time. Areas used as fishing businesses need to know how the level of utilization. For this reason, clear information is needed on the potential and level of utilization of marine fisheries resources to support the management policy of tuna resources for optimal management and utilization and to prevent the reduction of fish stocks in the future. This research was conducted for three weeks in July 2023 at Bungus Ocean Fishing Port (PPS), Padang City, West Sumatra Province. The method used in this research is a survey method or direct review of the field. The maximum sustainable potential value was obtained at 572.36 tons with an optimum utilization effort value of 330 trips. The allowable catch of longtail tuna is 457.89 tons, with an average utilization rate of 97.41%. Based on the average value of the utilization rate obtained from 2018 to 2019, the number of allowable catches, and the MSY value, it is concluded that the longtail tuna caught by bagan boats and Tonda fishing rods at PPS Bungus has experienced overfishing. There is a need for more action and monitoring of the amount of catch obtained each year, as well as limiting the amount of catch allowed for each fisherman so that the utilization rate of longtail tuna can return to optimal catch and prevent overfishing and maintain fish stocks for the future